The Sihailongwan Maar Lake, northeastern China as a candidate Global boundary Stratotype Section and Point for the Anthropocene series. (April 2023) - Han, Yongming; Zhisheng, An; Lei, Dewen; Zhou, Weijian; Zhang, Luyuan; Zhao, Xue; Yan, Dongna; Arimoto, Richard; Rose, Neil L; Roberts, Sarah L; Li, Li; Tang, Yalan; et al.
Sihailongwan Maar Lake, located in Northeast China, is a candidate Global boundary Stratotype Section and Point (GSSP) for demarcation of the Anthropocene. The lake's varved sediments are formed by alternating allogenic atmospheric inputs and authigenic lake processes and store a record of environmental and human impacts at a continental-global scale. Varve counting and radiometric dating provided a precise annual-resolution sediment chronology for the site. Time series records of radioactive ( 239, 240 Pu, 129 I and soot 14 C), chemical (spheroidal carbonaceous particles, polycyclic aromatic hydrocarbons, soot, heavy metals, δ 13 C, etc.), physical (magnetic susceptibility and grayscale) and biological (environmental DNA) indicators all show rapid changes in the mid-20th century, coincident with clear lithological changes of the sediments. Statistical analyses of these proxies show a tipping point in 1954 CE. 239, 240 Pu activities follow a typical unimodal globally-distributed profile, and are proposed as the primary marker for the Anthropocene. A rapid increase in 239, 240 Pu activities at 88 mm depth in core SHLW21-Fr-13 (1953 CE) is synchronous with rapid changes of other anthropogenic proxies and the Great Acceleration, marking the onset of the Anthropocene. The results indicate that Sihailongwan Maar Lake is an ideal site for the Anthropocene GSSP.